2015
DOI: 10.1038/jhg.2015.1
|View full text |Cite
|
Sign up to set email alerts
|

Novel microduplications at Xp11.22 including HUWE1: clinical and molecular insights into these genomic rearrangements associated with intellectual disability

Abstract: Recently, we defined a minimal overlapping region for causal Xp11.22 copy number gains in males with intellectual disability (ID), and identified HECT, UBA and WWE domain-containing protein-1 (HUWE1) as the primary dosage-sensitive gene, whose overexpression leads to ID. In the present study, we used this minimal interval to search for HUWE1 copy number variations by quantitative polymerase chain reaction in a large cohort of Brazilian males with idiopathic ID. We detected two unrelated sporadic individuals wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 9 publications
3
17
1
3
Order By: Relevance
“…HUWE1 is a HECT domain containing ubiquitin ligase, and recent studies showed that it plays important roles in cancer development, spermatogenesis and stem cell differentiation1261415. In the current study, our result shows that Huwe1 is expressed in mouse preimplantation embryo, and its expression is regulated by low oxygen concentration during early embryo development.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…HUWE1 is a HECT domain containing ubiquitin ligase, and recent studies showed that it plays important roles in cancer development, spermatogenesis and stem cell differentiation1261415. In the current study, our result shows that Huwe1 is expressed in mouse preimplantation embryo, and its expression is regulated by low oxygen concentration during early embryo development.…”
Section: Discussionsupporting
confidence: 54%
“…Cul4b, an X-linked mental retardation protein, was also shown to be critical for extra-embryonic tissue development, while dispensable for embryo proper development2122. Since both Cul4b and HUWE1 are involved in the X-linked mental retardation, it would be interesting to generate embryo specific and extra-embryonic tissue specific knock out mice and check whether they have neuron specific phenotype2614. It would also be valuable to check the three layers’ development in Huwe1 knock out embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this study also performed qPCR and showed that HUWE1 expression levels were elevated in these patient samples, consistent with an overexpression/gain-of-function effect on HUWE1. Subsequent studies that used exome or next generation sequencing identified HUWE1 CNVs in numerous other families with non-syndromic ID [66][67][68][69][70][71][72][73][74][75] (Table 1).…”
Section: Huwe1 Copy Number Variations and Nonsyndromic Intellectual Dmentioning
confidence: 99%
“…Individuals with HUWE1 CNVs sometimes have other neurodevelopmental conditions that accompany ID. The most compelling links are to epilepsy or seizure [64,67,[69][70][71][72][73][74]. Autism-like behaviors have also been documented [66,70,72].…”
Section: Huwe1 Copy Number Variations and Nonsyndromic Intellectual Dmentioning
confidence: 99%
“…Different cases of Xp duplication, that include the duplicated region described here, have been reported. 6,7,[20][21][22][23][24][25][26][27][28][29][30][31][32] However, in most cases a larger part of Xp, compared with our submicroscopic duplication, is involved. In our patient, the size of duplicated region of Xp is 363 kb and it extends from 53.475.904 nucleotide to 53.838.767 nucleotide.…”
Section: Discussionmentioning
confidence: 57%